Fungal pathogen associated with Rhizophora apiculta a comprative study between oiled and unoiled sites within Taklong Island National Marine Reserved (TINMAR), Nueva Valencia, Guimaras. - Repizo, Eunice Raiza C
Mangroves are exceptionally adaptable and therefore can survive under a relatively wide range of environmental conditions. They occur along sheltered tropical and subtropical coastlines. They are highly productive ecosystems next to the coral reefs and provide energy to marine habitats through production and decomposition of plant detritus. Mangrove are also the most prone to oiling due to accidental spills from tanks, pipelines, etc. Majority of the research on impacts of oil spills on mangroves focused on the immediate post-spill acute effects. In addition, the persistence of oil in sediments at oil spill sites has been reported in a number of published works. As such, these remaining oil could serve as source of stress to mangroves resulting into the experession of sub-lethal effects such as changes in foliage and canopy, abnormalities in reproductive structures among others. However, oil in mangroves also has the potential of increasing fungal attacks due to their impairment of natural defense mechamisms such as salt removal from leaves and trunks. Thus, this study was conducted to determine if there was a difference in fungal species composition and frequency of occurrence of species of mangroves collected in oiled and unoiled areas within Taklong Island National marine Reserve, Nueva Valencia, Guimaras following the spill that occurred in August 11, 2006. Fungi from diseased leaves of Rhizophora apiculata were isolated and characterized using Acidified Potato Dextros Agar APDA) for samples collected in January 2009 only. A total of 13 and 12 species were identified among the islates in oiled and unoiled sites, respectively. The result shows that there is a difference in species composition. Species occuring very frequent (>10 percent frequency of occurrence ) are different (except in Aspergillus wentii and Trichoderma sp.) in the oiled sites than the unoiled sites. Aspergillus wentii (18.92 percent), Aspergillus terreus (14.86 percent), Nigrospora sp. (12.16 percent), Aureobasidium pullulans (12.16 percent), Mucor plumbeus (12.16 percent), and Trichoderma sp.(10.81 percent)were the very frequently isolated species in unoiled sites while Aspergillus wetii (23.21 percent), Scopularopsis brevicula (12.5 percent), Trichoderma sp. (17.86 percent) and Mortieralla isabellina (10.71 percent) composed the very frequent species among samples collected from oiled sites. The resutls may imply that difference in frequency of occurrence of certain species might be an indicator for sub-lethal effects of oil but needs further investigations to consider environmental factors among others.